The Effects of Trunk Cavity and Air-Gaps in the Acoustic Response of a Passenger Vehicle - OKTAV, Akın (Archives of Acoustics, 2017)
The effects of additional cavities and air-gaps in the acoustic response of a passenger vehicle are investigated. It is observed that the cabin cavity and the trunk cavity of the passenger vehicle are connected through an aperture in the rear seat. In the trunk cavity of the vehicle, there are two more air-gaps which are designed as countermeasures to trunk lid slam noise. It is established that acoustic modes and acoustic eigenfrequencies of the vehicle are altered through the trunk cavity and its air-gaps. To develop an analytical solution, the actual acoustic cavity is simplified into a rectangular shape. In the analytical solution, the coupling of trunk and cabin cavities is considered. It is shown that the computational analysis results match well with the results of the analytical solution proposed. Further, the resonator effect of air-gaps present in the trunk cavity is examined.